Examining the Long-Run Impacts of Racial Terror with Data on Historical Lynchings of Mexicans in Texas - Francisca M. Antman; Brian Duncan (Institute of Labor Economics (IZA), 2024)
We merge the longitudinally linked historical U.S. Census records with data on lynchings of Hispanics in Texas to investigate the impacts of historical lynchings of ethnic Mexicans in Texas on U.S.-born Mexicans Americans. Using variation in lynching incidents across counties over time, we explore the impacts of local exposure to lynchings during childhood on long-run outcomes such as earnings, education, and home ownership of adults in 1940. Our findings are suggestive of small, negative impacts, but we caution that more research in this area is needed for a more robust interpretation of the results.
Keywords: J15; N31; N32; I2; 330; historical lynchings; Mexican Americans; Texas